Biotechnology of Hairy Root Systems - Doran, Pauline M.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Victor P. Bulgakov, Yuri N. Shkryl, Galina N. Veremeichik, Tatiana Y. Gorpenchenko and Yuliya V. Vereshchagina: Recent Advances in the Understanding of Agrobacterium rhizogenes-Derived Genes and Their Effects on Stress Resistance and Plant Metabolism. Le Zhao, Guy W. Sander and Jacqueline V. Shanks: Perspectives of the Metabolic Engineering of Terpenoid Indole Alkaloids in Catharanthus roseus Hairy Roots. Jian Wen Wang and Jian Yong Wu: Effective Elicitors and Process Strategies for Enhancement of Secondary Metabolite Production in Hairy Root Cultures. Amanda R. Stiles and Chun-Zhao Liu: Hairy Root Culture: Bioreactor Design and Process Intensification. Marina Skarjinskaia, Karen Ruby, Adriana Araujo, Karina Taylor, Vengadesan Gopalasamy-Raju, Konstantin Musiychuk, Jessica A. Chichester, Gene A. Palmer, Patricia de la Rosa, Vadim Mett, Natalia Ugulava, Stephen J. Streatfield and Vidadi Yusibov: Hairy Roots as a Vaccine Production and Delivery System. Zahwa Al-Shalabi and Pauline M. Doran: Metal Uptake and Nanoparticle Synthesis in Hairy Root Cultures.
Recent Advances in the Understanding of Agrobacterium rhizogenes-Derived Genes and Their Effects on Stress Resistance and Plant Metabolism -- Perspectives of the Metabolic Engineering of Terpenoid Indole Alkaloids in Catharanthus roseus Hairy Roots -- Effective Elicitors and Process Strategies for Enhancement of Secondary Metabolite Production in Hairy Root Cultures -- Hairy Root Culture: Bioreactor Design and Process Intensification -- Hairy Roots as a Vaccine Production and Delivery System -- Metal Uptake and Nanoparticle Synthesis in Hairy Root Cultures.
Keywords: Medicine; Vaccines; Biotechnology; Plant breeding; Biomedicine; Vaccine; Biotechnology; Plant Genetics & Genomics